Gray matter correlates of behavioral severity in progressive supranuclear palsy - Josephs, Keith A.; Whitwell, Jennifer L.; Eggers, Scott D.; Senjem, Matthew L.; Jack Jr, Clifford R. (Movement disorders, 2011)
Background: Behavioral changes occur in progressive supranuclear palsy. This study aimed to identify the anatomic correlate of behavioral severity in progressive supranuclear palsy. Methods: We performed standardized tests of behavioral severity (Frontal Behavioral Inventory), cognitive severity (Mini‐Mental State Examination), motor severity (Movement Disorder Society‐sponsored revision of the Unified Parkinson's Disease Rating Scale Part III), and a 3.0‐T volumetric head magnetic resonance imaging scan in 18 prospectively recruited subjects meeting National Institute of Neurological Diseases and Stroke‐Society of Progressive Supranuclear Palsy criteria for probable progressive supranuclear palsy. Atlas‐based parcellation was utilized to obtain regional gray matter volumes of frontal, temporal, and parietal lobe, and caudate and putamen, and voxel‐based morphometry was used to assess voxel‐level gray matter loss. We performed correlation analyses between total Frontal Behavioral Inventory score and gray matter volume, as well as assessed gray matter volume across three groups defined according to behavioral severity (mild, moderate, and severe) based on total Frontal Behavioral Inventory score. Results: Specific behaviors, with the exception of apathy that occurred in 83% of the subjects, were relatively infrequent. There was no association between Frontal Behavioral Inventory and cognitive or motor severity. Regions of the frontal lobe, particularly, the lateral posterior frontal cortex, significantly correlated with the total Frontal Behavioral Inventory score when using both regional volume and voxel‐level analyses. The groupwise analyses also supported these findings. The presence of apathy correlated with atrophy of the putamen. Discussion: Behavioral severity in progressive supranuclear palsy appears to be associated with volume loss of frontostriatal regions, in particular, lateral posterior frontal lobe and putamen. © 2011 Movement Disorder Society